Celebrating World Tuberculosis Day at the time of COVID-19. Issue 4 (23rd April 2020) - Alagna, Riccardo; Besozzi, Giorgio; Codecasa, Luigi Ruffo; Gori, Andrea; Migliori, Giovanni Battista; Raviglione, Mario; Cirillo, Daniela Maria
World Tuberculosis Day, observed on 24 March each year, is the global call to raise awareness, celebrate successes and remind the world that tuberculosis (TB) is still the number one killer among the infectious causes of death [1]. TB is a preventable and curable disease, and its control is a highly cost-effective health intervention. However, diagnostic delay and inadequate treatment contribute to the severity and mortality of the disease as well as the risk of transmission and development of drug resistance. Despite the fact that TB disproportionately impacts low- and middle-income countries, it does not spare any country in the world, including those in the European Union/European Economic Area, where more than 4000 people still die from the disease every year [2]. Moreover, the high number of multidrug-resistant (MDR)-TB cases in some countries of the World Health Organization (WHO) European Region poses a growing public health threat. Despite the sheer numbers, TB has for too long been overshadowed by HIV and malaria, and currently by the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) responsible for the coronavirus disease 2019 (COVID-19) epidemic. TB remains a global health emergency https://bit.ly/39DqHTb